Nitrogen management in wastewater industry from circular economy perspective - Chai, Matthias Zheng Feng (2022)
The municipal wastewater industry is known as a resourceful hub as it contains large amount of valuable nitrogen that can be recovered. However, the operation of conventional nitrogen management in the municipal wastewater industry is by nitrogen removal, mainly through biological nitrogen removal (BNR) processes. The downside of BNR processes includes high energy and cost requirement, and the emission of greenhouse gases (GHGs) only served the purpose of meeting the standard discharge limit of nitrogen. Besides, the sole reliance on energy-intensive Haber-Bosch process to produce synthetic fertilizers triggered the eminent nitrogen recovery process. Therefore, existing nitrogen recovery pathways were explored in the municipal wastewater industry for the production of useful bioproducts. The pathways reviewed in this project included bio-membrane integrated systems (BMISs), capacitive deionization (CDI), coupled aerobic-anoxic decomposition operation (CANDO) process, ammonium recovery through adsorbents, stripping and struvite precipitation, and through the usage of microalgae and cyanobacteria. The feasibility and challenges of its implementation were explored, in which low-strength of municipal wastewater being the major challenge causing economical and technical infeasibility in large-scale execution. Amongst the pathways reviewed, the BMISs, FCDI and stripping and struvite precipitation were discovered to be the potential pathways for large-scale application. Therefore, more intensive research and development should be conducted for these recovery technologies for the techno-economic viability, coupled with other initiatives such as governmental incentives and transparent communication between involved parties that includes local farmers, research scientists, stakeholders and consumer for the successful implementation of nitrogen recovery pathways.